Changes in surface soil properties of a notilled tropical Alfisol due to intercropping maize, cassava and egusi melon - Hulugalle, N.; Ezumah, H.C.; Leyman, T. (Elsevier, 1994)
Changes in earthworm activity, water runoff, soil erosion, soil physical properties and fertility, and crop growth and yield caused by intercropping either maize (Zea mays L.) and cassava (Manihot esculenta Crantz) (MC) or maize, cassava and 'egusi' melon (Citrullus lanatus Thunb.) (MCM) on no-tilled and handhoe-tilled plots were studied in an Alfisol in southwestern Nigeria. Runoff and erosion in no-tilled plots were negligible and were not affected by cropping system. Similarly, soil compaction and infiltration which were lower and higher, respectively, in no-tilled plots than in tilled plots were also unaffected by cropping system. With tillage, however, MCM resulted in lower penetrometer resistance in the soil and erosion than MC, although water infiltration was unaffected. Maximum diurnal soil temperatures were lower with MCM, with lowest values being observed when combined with no-tillage. Similarly, soil fertility was greater with MCM, with highest fertility occurring in no-tilled plots. Combination of no-tillage with MCM resulted, therefore, in a soil environment which was least compacted, most fertile, cooler, had higher water infiltration rates and where water runoff and soil erosion rates were negligible. Inclusion of melon in the crop mixture did not affect grain yield of maize, but reduced cassava tuber yield. Reduction in tuber yield was of the order of 19%.